Neea bradeana (Nyctaginaceae: Pisonieae), a new species with whorled leaf arrangement from the Atlantic Forest of Southeastern Brazil - Sandoli Rossetto, Elson Felipe; Da Silva Costa, Daniel; Ferraz, José Roberto (Phytotaxa, 2024)
Neea bradeana is here described for the Atlantic Rainforest of Southeastern Brazil. This new species had been confused for decades with N. verticillata, the type species of the genus which is described for Peru. N. bradeana is characterized by its unbranched shrubs with whorled sessile or short-petiolate leaves and erect-congested inflorescences. This species is here described and illustrated; remarks on taxonomic and morphologic affinities, distribution map, and conservation assessment are also provided.